2020
DOI: 10.1210/clinem/dgaa484
|View full text |Cite
|
Sign up to set email alerts
|

International Histopathology Consensus for Unilateral Primary Aldosteronism

Abstract: Objective Develop a consensus for the nomenclature and definition of adrenal histopathologic features in unilateral primary aldosteronism (PA) Context Unilateral PA is the most common surgically-treated form of hypertension. Morphologic examination combined with CYP11B2 (aldosterone synthase) immunostaining reveals diverse histopathologic features of lesions in the resected adrenals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
214
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(228 citation statements)
references
References 28 publications
10
214
1
3
Order By: Relevance
“…Based on the statement of international consensus on PA histopathology, aldosterone-producing non-neoplastic nodules are further classified into APMs and aldosterone-producing nodules www.e-enm.org 17 (APNs) according to whether the nodule is visible (detected) by H&E section (APN was defined as visible nodules) or not, although both types preserve the polarity of zonation, including the gradient of the pattern of CYP11B2 immunoreactivity from the outer to inner part [6]. The previously proposed classifications of "APCC" and/or "micronodule" have been reported to be difficult to distinguish from each other by histopathological findings including CYP11B2 immunohistochemistry alone, and required relevant clinical information such as the presence or absence of hypertension and/or PA.…”
Section: Aldosterone-producing Non-neoplastic Nodules (Apms and Apns)mentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the statement of international consensus on PA histopathology, aldosterone-producing non-neoplastic nodules are further classified into APMs and aldosterone-producing nodules www.e-enm.org 17 (APNs) according to whether the nodule is visible (detected) by H&E section (APN was defined as visible nodules) or not, although both types preserve the polarity of zonation, including the gradient of the pattern of CYP11B2 immunoreactivity from the outer to inner part [6]. The previously proposed classifications of "APCC" and/or "micronodule" have been reported to be difficult to distinguish from each other by histopathological findings including CYP11B2 immunohistochemistry alone, and required relevant clinical information such as the presence or absence of hypertension and/or PA.…”
Section: Aldosterone-producing Non-neoplastic Nodules (Apms and Apns)mentioning
confidence: 99%
“…APAs are solitary neoplasms usually measuring more than 10 mm in their greatest dimension and histologically composed of both compact and clear cells with immense intratumoral heterogeneity in their morphological features. The definition of APAs should be based upon both clinical information and histopathological features, including CYP11B2-positive immunoreactivity [ 6 ]. We previously reported that KCNJ5 mutated APAs mostly consisted of clear cells [ 38 ].…”
Section: Histopathology and Cellular Morphology Of Pamentioning
confidence: 99%
See 3 more Smart Citations